Linear scleroderma "en coup de sabre" coexisting with plaque-morphea: neuroradiological manifestation and response to corticosteroids. Issue 5 (1st May 2003) - Unterberger, I; Trinka, E; Engelhardt, K; Muigg, A; Eller, P; Wagner, M; Sepp, N; Bauer, G
Abstract : A 24 year old woman in the 33rd week of pregnancy developed progressive neurological complications with right sided hemiparesis in association with the occurrence of linear scleroderma "en coup de sabre" (LSCS) and pre-existing plaque-morphea, already being treated by balneophototherapy. Further progression of neurological symptoms led to a caesarean section with the delivery of a healthy child. Brain magnetic resonance imaging (MRI) showed focal T2 signal increases in the left frontoparietal region directly adjacent to the area of LSCS. Cerebrospinal fluid analysis revealed oligoclonal bands, suggesting an intracerebral inflammatory process. Subsequent pulsed corticosteroid treatment led to a remission of neurological symptoms and to a marked resolution of the MRI lesions.